Matrix metalloproteinase MMP-8, TIMP-1 and MMP-8/TIMP-1 ratio in plasma in methicillin-sensitive Staphylococcus aureus bacteremia. - Erik Forsblom (Public Library of Science (PLoS), 2021)
Background Matrix metalloproteinase-8 (MMP-8) and tissue inhibitor of metalloproteinases-1 (TIMP-1) have been shown to predict prognosis in sepsis. However, MMP-8 and TIMP-1 in Staphylococcus aureus bacteremia (SAB) lacks evaluation and their role in the pathogenesis of SAB is unclear. Methods MMP-8 and TIMP-1 and MMP-8/TIMP-1 molar ratio were determined at days 3, 5 and 28 from positive blood cultures in patients with methicillin-sensitive SAB and the connection to disease severity and early mortality was determined. Results Altogether 395 SAB patients were included. Patients with severe sepsis or infection focus presented higher MMP-8 levels at day 3 and 5 (p<0.01). Higher day 3 and 5 MMP-8 levels were associated to mortality at day 14 and 28 (p<0.01) and day 90 (p<0.05). Day 3 MMP-8 cut-off value of 203 ng/ml predicted death within 14 days with an area under the curve (AUC) of 0.70 (95% CI 0.57-0.82) (p<0.01). Day 5 MMP-8 cut-off value of 239 ng/ml predicted death within 14 days with an AUC of 0.76 (95% CI 0.65-0.87) (p<0.001). The results for MMP-8/TIMP-1 resembled that of MMP-8. TIMP-1 had no prognostic impact. In Cox regression analysis day 3 or 5 MMP-8 or day 3 MMP-8/TIMP-1 had no prognostic impact whereas day 5 MMP-8/TIMP-1 predicted mortality within 14 days (HR, 4.71; CI, 95% 1.67-13.3; p<0.01). Conclusion MMP-8 and MMP-8/TIMP-1 ratio were high 3-5 days after MS-SAB diagnosis in patients with an infection focus, severe sepsis or mortality within 14 days suggesting that matrix metalloproteinase activation might play a role in severe SAB.